Local Wisdom and Civic Virtue: The Ceprotan Tradition as a Model for Internalizing Pancasila Values in Indonesia - Wilis, Roro; Wiratmoko, Dheny; Padang, Bonita; Parhamah, Winda Pitriani; Kinanti, Ajeng Diah (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
This study investigates the Ceprotan tradition in Sekar Village, Donorojo District, Pacitan Regency, and its connection to Pancasila values, focusing on how character values are internalized to foster spiritual obedience and social harmony. Using a qualitative ethnographic approach, data were collected through interviews with village and community leaders, tradition participants, and direct observation of religious practices. Findings show how the Ceprotan tradition embodies the five pillars of Pancasila through collective community practices. Divinity is expressed as a symbol of gratitude to God and protection from evil, reflected in the community’s reverence for ancestors. Humanity is marked by respect for equal rights and the preservation of legendary narratives that shape social order. Unity manifests through strong solidarity and social cohesion. Democracy emerges from the community’s ability to adapt and modify rituals by consensus, while social justice is evident in the equitable division of labor, regardless of socioeconomic status. The internalization of these values occurs through four interconnected stages: social experience, emotional engagement, cultural reflection, and the transmission of values across generations. This research makes a significant scholarly and practical contribution by providing a culturally grounded framework for integrating Pancasila values into character education and civic development. It demonstrates that indigenous traditions, such as Ceprotan, are not merely cultural artifacts but active vehicles for strengthening national identity, shaping value-based community practices, and guiding policymakers to embed local wisdom in educational curricula and social programs.